ANALYSIS AND INTERPRETATION RESEARCH RESULTS (Pedagogy of Higher and Secondary Education, 2008)
Forming experiment of this probe has proves usage the personal rough approach for creation of indispensable qualities for the future managers o f entrepreneurial business.